THE ROLE OF PESANTREN IN THE EMPLOYMENT OF WORKERS IN THE INDUSTRIAL ERA 4.0 : (Study at Pondok Pesantren Attanwir Bojonegoro) - Mundhori; Syam, Nur; Humaidi, Anis (Jurnal Studi Pesantren, 2024)
This article aims to explore the role of Pondok Pesantren Attanwir Bojonegoro in absorbing labor in the Industry 4.0 era. The study focuses on the transformation of Pondok Pesantren Attanwir from a traditional institution to a modern institution, and the efforts made by the institution to develop the creativity of its students. The article also discusses the challenges and prospects of pesantren in character education in the Industry 4.0 era. This research uses a qualitative approach with data collected through observation, interviews, and documentation. The research findings show that Pondok Pesantren Attanwir has played an important role in absorbing the workforce in the Industry 4.0 era by equipping its students with the necessary skills and knowledge to adapt to the ever-changing job market. Keywords: Pesantren, Labor Absorption, Industrial Era 4.0